A Class of Lightlike Hypersurface of Meta-metallic Pseudo-Riemannian Manifolds - Mahamane Saminou Ali; Zakary Dan Azoumi Ali; Mouhamadou Hassirou (International Journal of Mathematics And its Applications, 2025)
The purpose of the present paper is to focus hypersurfaces using the meta-metallic-chi ratio. We study some properties of a structure induced on a hypersurface by a meta-metallic structure. We revisit the invariant hypersurfaces of a meta-metallic pseudo-Riemannian manifold, we deduce some properties of this type of hypersurface and we close with an example.